Anatomické ilustrace spisu Leonarda Ferdinanda Meisnera z Löwenberku - Marie Vymazalová (Acta Universitatis Carolinae: Historia Universitatis Carolinae Pragensis)
This contribution is dedicated to a set of anatomical drawings preserved in the manuscript of Leonard Ferdinand Meisner from 1690. Meisner’s work was based on the lectures by a Prague physician and university teacher Joannes Antonio Cassinis de Bugella. The anatomical drawings are analysed in the context of other surviving drawings in Czech collections. The context of their origin, sources of inspiration, and artistic qualities are also dealt. The drawings were not created as records of dissections performed during university lectures; rather, they served as a supplementary teaching material accompanying a tractate on anatomy. They are the work of several hands, and their quality varies.